2022
DOI: 10.1186/s13054-022-04211-w
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal phenotypes in patients with acute respiratory distress syndrome: a multi-database study

Abstract: Background Previously identified phenotypes of acute respiratory distress syndrome (ARDS) have been limited by a disregard for temporal dynamics. We aimed to identify longitudinal phenotypes in ARDS to test the prognostic and predictive enrichment of longitudinal phenotypes, and to develop simplified models for phenotype identification. Methods We conducted a multi-database study based on the Chinese Database in Intensive Care (CDIC) and four ARDS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…ARDS is a heterogeneous syndrome involving different phenotypes with distinct clinical and outcome characteristics. We previously identified three novel ARDS phenotypes with different severity of pulmonary mechanics and found that the association between pulmonary parameters and mortality varied within phenotypes [ 7 ]. Lung morphology is another crucial aspect in distinguishing specific ARDS phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…ARDS is a heterogeneous syndrome involving different phenotypes with distinct clinical and outcome characteristics. We previously identified three novel ARDS phenotypes with different severity of pulmonary mechanics and found that the association between pulmonary parameters and mortality varied within phenotypes [ 7 ]. Lung morphology is another crucial aspect in distinguishing specific ARDS phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Bos et al did discover two trajectories related to ventilatory ratio and mechanical power that could potentially predict the duration of mechanical ventilation and the risk of death [16]. More recently, Chen and colleagues [37] described 3 longitudinal phenotypes with several changes between phenotypes during the first 4 days. Lu et al analyzed the incidence of sub-phenotypes and their trajectories during 10 days according to respiratory support [38].…”
Section: Discussionmentioning
confidence: 99%
“…[3] At the same time, the large pulmonary embolism load caused a sharp increase in the patient's pulmonary artery pressure leading to right Both of the two theories may lead to the tachycardia, rapid pulse, high fever, sudden platelet reduction, oliguria and other clinical symptoms in our patient. [4] The clinical manifestations of FES are respiratory distress, nervous system changes, and petechial rash. This patient met the diagnostic criteria proposed by Gurd, [5] with the respiratory symptoms and positive signs of lung imaging changes.…”
Section: Discussionmentioning
confidence: 99%